Two-Size Moment Multi-Fluid Model: A Robust and High-Fidelity Description of Polydisperse Moderately Dense Evaporating Sprays (Communications in Computational Physics, 2018)
High fidelity modeling and simulation of moderately dense sprays at relativelylow cost is still a major challenge for many applications. For that purpose, weintroduce a new multi-fluid model based on a two-size moment formalism in sections,which are size intervals of discretization. It is derived from a Boltzmann type equationtaking into account drag, evaporation and coalescence, which are representative ofthe complex terms that arise in multi-physics environments. The closure of the modelcomes from a reconstruction of the distribution. A piecewise affine reconstruction insize is thoroughly analyzed in terms of stability and accuracy, a key point for a high-fidelityand reliable description of the spray. Robust and accurate numerical methodsare then developed, ensuring the realizability of the moments. The model and methodare proven to describe the spray with a high accuracy in size and size-conditionedvariables, resorting to a lower number of sections compared to one size moment methods.Moreover, robustness is ensured with efficient and tractable algorithms despitethe numerous couplings and various algebra thanks to a tailored overall strategy. Thisstrategy is successfully tested on a difficult 2D unsteady case, which proves the efficiency of the modeling and numerical choices.